CONSUMER BEHAVIOR AND PROFIT MAXIMIZATION (Web of Technology: Multidimensional Research Journal, 2024)
In this article, we explore the relationship between consumer behavior and the profit maximization strategies used by businesses. By analyzing how consumer preferences, purchasing habits, and decision-making processes influence demand, we consider the various approaches businesses can take to align their marketing and operational strategies with consumer trends. Key elements such as pricing strategies, product differentiation, and customer loyalty programs are discussed in the context of their impact on revenue generation and market share. We conclude the article by highlighting the importance of understanding consumer psychology to ensure sustainable business growth and optimize profitability.